Critical components identification using analytic hierarchy process - a case study towards product design improvement / \c Nurul Hidayah binti Junaidi. - Nurul Hidayah Junaidi (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2017)
The main research objective for this study is to develop the critical component identification decision model for product design improvement. The model will assist designer to identify the critical components towards product design improvement. The specific objectives of this study are highlight as the following ; to propose the critical component identification decision model by using Analytic Hierarchy Process (AHP) ; to validate the critical component decision model by using case study of different type of staple gun.